Resprouting of native species from Cerrado: a structural perspective - Silva, Gabriela Santos da (2022)
Resprouting is considered the most important regenerative trait for vegetation persistency as a response to environmental disturbances, which are considered common in Cerrado. This functional trait depends on the development, the protection degree of buds, and also the mobilization of storage compounds presents in the belowground systems. Nowadays, one of the most severe threats to Cerrado vegetation is the cultivation of commercial exotic species, such as Pinus sp., which drastically reduce the occurrence and development of native species due to their highly competitive capacity. This situation has been occurring at the Santa Bárbara Ecological Station (EEcSB), Águas de Santa Bárbara - São Paulo, where there are Pinus sp. plantations since the 1970s. Due to the negative impact of Pinus sp. on the Cerrado vegetation, the EEcSB management plan (2011) has been working to gradually eliminate the exotic species with the purpose of regenerate the native species. Since this action, native species such as the palms Allagoptera campestris (Mart.) Kuntze and Syagrus loefgrenii Glassman have been resprouting mainly in those areas where the remaining material was burned after the clear-cutting of the trees. In addition, it is possible to observe the presence of these palms coexisting in the understory of Pinus sp. However, there are gaps in the features that confer resilience and promote the regeneration of these plants. Thus, the present study aimed to answer the following questions: a) Which are the structural features that allowed the resprouting of Myrtaceae species after years of the aerial organs being suppressed by the presence of pine trees? b) After the resprouting, how meristematic tissues are protected in aerial buds (terminal, axillary, and accessory) in the regenerating environment? c) Which are the adaptations of palm species that allow them to colonize and grow under areas with different disturbance histories? d) Are the palms able to resprout in the disturbed areas after the introduction of a new perturbation?